The Values of Multicultural Islamic Religious Education in Homeschooling Organizing Institutions (Case Study at the Kak Seto Homeschooling organizer) - Syarifah (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to determine the values of multicultural Islamic religious education in homeschooling institutions (a case study in Kak Seto's homeschooling institutions). This study concluded that in Kak Seto's homeschooling there are values of multicultural Islamic religious education. Thus they recognize and respect differences which are not merely recognition of equality, but are also related to respect for differences in the way of living and worshiping according to the basis of just and civilized humanity. So that the purity and uniqueness of each religious community, even though they differ in their patterns of thought and religion, they can live together in harmony, still help each other, and educate them to become individuals who are grateful to their God. So that later when they are in society they can maintain and maintain peace.